Implementasi KPI dan Perancangan Sistem e-KPI pada PT. XYZ - Kevin Chevalia (Jurnal Titra, 2016)
This study was conducted to implement the KPI and design e-KPI system at PT. XYZ. KPIs are implemented using the basic four perspectives based on the Balanced Scorecard. The initial condition, the company has KPI for two divisions from six divisions and also the absence of a system of e-KPI. The result shows that six divisions have implemented KPI and e-KPI system has been designed at PT. XYZ. KPI will be assessed for performance appraisal on PT. XYZ for a period of time to come. e-KPI system provides the facility to the management to access KPI of division/department anytime and anywhere.